2020
DOI: 10.1007/s41999-020-00337-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of replacement questions for slowness and weakness to assess the Fried Phenotype: a cross-sectional study

Abstract: Purpose When screening large populations, performance-based measures can be difficult to conduct because they are time consuming and costly, and require well-trained assessors. The aim of the present study is to validate a set of questions replacing the performance-based measures slowness and weakness as part of the Fried frailty phenotype (FRIED-P). Methods A cross-sectional study was conducted among community-dwelling older adults (≥ 60 years) in three Flemish municipalities. The Fried Phenotype (FRIED-P) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
(61 reference statements)
3
12
0
Order By: Relevance
“…For prefrailty diagnostics, the Mod-FP was also better at discriminating nonprefrail (specificity of 92%) than prefrail (sensitivity of 77%) PWH at a cutoff of one component. These results are consistent with a study by Van der Elst et al (2020) evaluating the substitution of the functional status measures with self-reported questions. Van der Elst and colleagues hypothesized that these differences in sensitivity and specificity may be indicators of people overestimating their physical health/status in self-report compared with their performance-based assessment results, which may also be the case in our cohort.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For prefrailty diagnostics, the Mod-FP was also better at discriminating nonprefrail (specificity of 92%) than prefrail (sensitivity of 77%) PWH at a cutoff of one component. These results are consistent with a study by Van der Elst et al (2020) evaluating the substitution of the functional status measures with self-reported questions. Van der Elst and colleagues hypothesized that these differences in sensitivity and specificity may be indicators of people overestimating their physical health/status in self-report compared with their performance-based assessment results, which may also be the case in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The agreement between the phenotypes was substantial in all weighting schemes (Cohen's kappa ranged from 0.64 to 0.75). Our results were similar to the study by Van der Elst et al (2020), although they included replacement questions for both weakness and slowness, whereas we replaced slowness and excluded weakness from the Mod-FP. We also confirmed that the substitution of gait speed with the mobility PRO is reasonable.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…There is sufficient consensus (∼80%) and adequate precedent in the frailty literature for using rapid screens for individuals >70 years old (Morley et al, 2013). Sensitivity, specificity, positive and negative predictive values of the modified Fried phenotype were not calculated in this study, but it is reported elsewhere in smaller study samples (n = 124, n = 135, and n = 196), (Aprahamian et al, 2017;Op Het Veld et al, 2018;Van der Elst et al, 2020). We examined only three NHANES data cycles, and age groups were a categorical variable since the oldest age that could be reported was 80 years.…”
Section: Limitationsmentioning
confidence: 99%
“…For this reason, many clinicians still find this procedure time-consuming and potentially unpractical in the context of renal outpatient services [ 12 ]. To overcome this implementability issue, several researchers have designed alternative operationalisations of the Fried phenotype by replacing the performance-based measures with subjective (questionnaire-based) assessments in both CKD [ 16 ] and non-CKD populations [ 17 , 18 ]. Although these self-reported definitions of frailty perform well in predicting adverse outcomes [ 5 ], they are often less accurate than objective assessments of physical performance in diagnosing frailty in people living with CKD-5 [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%